The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.2134/jpa1998.0074
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fertilization of Cotton Produced on a Low K Soil with Contrasting Tillage Systems

Abstract: Correcting K deficiency in fast‐fruiting cotton (Gossypium hirsutum L.) cultivars requires information on growth response to available soil K, soil K2O rates, and supplemental foliar K. Field research was initiated in 1991 on a Memphis silt loam soil (fine‐silty, mixed, active, thermic Typic Hapludalf), low in Mehlich I extractable K, to evaluate cotton responses to soil‐and foliar‐applied K for conventional‐tillage (CT) and notillage (NT) production systems in Tennessee. Potassium rates of 0, 30, 60, and 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This may be a response to residual K carried over from previous years (Table 1). We suspect that three previous years of 16.4 kg K ha-1 yc 1 applied to foliage elevated soil K fertility sufficiently to elicit a canopy response in the fourth year, in the absence of soilapplied K. This is consistent with a companion study by Howard et a!. (1998), in which the greatest yield response to foliar K occurred with no soil-applied K fertilizer.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…This may be a response to residual K carried over from previous years (Table 1). We suspect that three previous years of 16.4 kg K ha-1 yc 1 applied to foliage elevated soil K fertility sufficiently to elicit a canopy response in the fourth year, in the absence of soilapplied K. This is consistent with a companion study by Howard et a!. (1998), in which the greatest yield response to foliar K occurred with no soil-applied K fertilizer.…”
Section: Resultssupporting
confidence: 84%
“…Foliar KN0 3 also increased lint yields in both years, but only in the absence of soil-applied K, as reflected in the soil X foliar treatment interactions for yield. In a companion study in which Ca(N0 3 ) 2 was also applied as a foliar treatment, Howard et al (1998) demonstrated that nearly all of the yield response to foliar KN0 3 was attributable to K rather than N. The relative yield response to KN0 3 was somewhat greater in the year of adequate rainfall (58%) than in the drought year of 1993 ( 42% ). In 1993, there was no significant earliness response to K, despite yield responses at both first and second harvest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations